Board of Directors Independence and Firm Value: Empirical Evidence Based on the Bucharest Stock Exchange Listed Companies - Vintila, Georgeta; Gherghina, Stefan Cristian (International Journal of Economics and Financial Issues, 2013)
<!--[if gte mso 9]> <![endif]--> This paper examines the influence and causal relationship between board of directors independence, CEO duality, and firm value. By estimating multivariate regression models for panel data, unbalanced, for a sample of companies listed on the Bucharest Stock Exchange, there resulted a positive influence of the percentage of independent directors on firm value, but down to a threshold of their representation of 47.23 percent, whereupon their influence becomes negative. When we employed fixed-effects models, the relationship previously mentioned was not statistically validated. However, the results provide support for a lack of statistically significant relationship between the percentage of non-executive directors and firm value. Besides, by estimating fixed-effects models we found a positive influence of CEO duality on industry-adjusted Tobin’s Q ratio, but not statistically significant when estimating models without cross-sectional effects. The causal relationships between board independence and firm value identified based on Granger causality are not robust. Keywords: independent directors; non-executive directors; firm value; panel data regression models; Granger causality; vector autoregression JEL Classifications: G32; G34 <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->